PERGULATAN HUKUM POSITIVISTIK MENUJU PARADIGMA HUKUM PROGRESIF - Gde Made Swardhana (Masalah-Masalah Hukum, 2010)
The legal reform is not only reform the legal substance but also to reform the legal structure and the legal culture including legal ethic and legal science. The impact of legal formalistic positivistic can not success to solve the legal problem in reality, therefore we need the progressive law to solve those problems. The chrematistic of Progressive Law consist of: (1). the paradigm of progressive law is law for human being; (2) the progressive law refuses the rigid of positivism; (3). If we recognize the rigid of positivism, we need space for freedom from formal law (positivism); (4). The progressive law pays attention and focus for human behavior regarding the existence of laws. Through some characteristics of progressive law, the law enforcement in Indonesia ideally is not only focus to the legal positivistic, but we should jump, reach, and come to the paradigm of progressive law